STUNTING DI DESA PLABUHAN KECAMATAN PLANDAAN KABUPATEN JOMBANG - Wahyuningsih, Endah; Mukari, Mukari; Susetiani, Arin Eka (WELL BEING, 2020)
Stunting is a condition in which toddlers experience failure in their growth and development due to insufficient nutrition. The research was conducted to abtain a complete potrait/ picture of stunting in village of Plabuhan.This research method is qualitative with informants consisting of mothers who have children under five with stunting, rural government, rural midwives and posyandu cadres. Data obtained from interviews and stunting data in the village. Data analysis with reduction, presentation, drawing conclusions.The result shows that stunting in the village of Plabuhan is caused by multiple factors ranging from economic factors, knowledge and also cultural factors.In a socio-cultural perspective, the condition of stunting that occurs is not considered as a sick condition so it requires special attention, the condition of stunting is understood as a condition that is accepted because of reasonableness where some of them have ancestors who are also short / small.